Preventing fraud in crypto payments - Louise Damkjær Christensen (Journal of Economic Criminology)
When paying with a payment instrument in fiat currency within the EU, the transaction is covered by the PSD2, which provides prudent protection for payers and their payment instruments. When the transaction is instead executed in bitcoin, an unbacked crypto-asset, the transaction is not covered by any EU regulation despite it being used as a method of payment for goods and other services. This leaves consumers in a bad position if their electronic wallet has been abused for fraudulent payments in unbacked crypto-assets as the victim bears the full loss and there is no option for rectification. Change is warranted around crypto payments as the current legal situation leaves consumers unprotected and vulnerable to digital economic crime. This article examines possible solutions to deter criminal activity in the crypto economy, and how to make financial regulation more adept to make crypto payments safer and protect payers in cases of payment fraud. The article concludes that crypto payment fraud is already criminalised in criminal legislation, but changes can be made in financial law to provide protection for the victims of crypto payment fraud.